2004
DOI: 10.1016/j.jalgebra.2004.07.023
|View full text |Cite
|
Sign up to set email alerts
|

An analogue of the Steinberg character for the general linear group over the integers modulo a prime power

Abstract: Lees, and independently Hill, described an irreducible character of GL n (Z/p h Z) for h > 1, which is an analogue of the Steinberg character in the h = 1 case. We give a new construction of this analogue. In particular, we prove that it is induced from the Steinberg character of an appropriate parabolic subgroup. Further, we use this to show that it has a characterisation identical to that given by Curtis to the Steinberg character.  2004 Elsevier Inc. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 8 publications
(10 reference statements)
0
15
0
Order By: Relevance
“…When Σ = A n , this reduces to the definition given in [2]. Further, Suzuki [24] showed that every subgroup of G containing B is of this form provided that κ has odd characteristic; q = 3 for types A 3 , B n , C n , D n and F 4 ; and char κ = 3 for type G 2 .…”
Section: Parabolic Subgroupsmentioning
confidence: 97%
See 4 more Smart Citations
“…When Σ = A n , this reduces to the definition given in [2]. Further, Suzuki [24] showed that every subgroup of G containing B is of this form provided that κ has odd characteristic; q = 3 for types A 3 , B n , C n , D n and F 4 ; and char κ = 3 for type G 2 .…”
Section: Parabolic Subgroupsmentioning
confidence: 97%
“…As in [2], the analogue of the Steinberg character will be described as an alternating sum of permutation characters over certain "parabolic" subgroups. This is similar to both Steinberg's original construction [20] for the general linear group and Curtis' later definition [5] for finite groups with BN-pair.…”
Section: Analoguementioning
confidence: 99%
See 3 more Smart Citations